2015
DOI: 10.1371/journal.pone.0141899
|View full text |Cite
|
Sign up to set email alerts
|

Functional Trait Changes, Productivity Shifts and Vegetation Stability in Mountain Grasslands during a Short-Term Warming

Abstract: Plant functional traits underlie vegetation responses to environmental changes such as global warming, and consequently influence ecosystem processes. While most of the existing studies focus on the effect of warming only on species diversity and productivity, we further investigated (i) how the structure of community plant functional traits in temperate grasslands respond to experimental warming, and (ii) whether species and functional diversity contribute to a greater stability of grasslands, in terms of veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 80 publications
(88 reference statements)
2
24
0
Order By: Relevance
“…Pfestorf et al. () and Debouk, de Bello, and Sebastià () both reported finding a more direct coupling between environmental drivers and plant functional traits than diversity. Aggregate ANPP in our study was stabilized through time by attributes linked to species identity and dominance rather than by species richness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pfestorf et al. () and Debouk, de Bello, and Sebastià () both reported finding a more direct coupling between environmental drivers and plant functional traits than diversity. Aggregate ANPP in our study was stabilized through time by attributes linked to species identity and dominance rather than by species richness.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Wilcox et al (2017) found no correlation between the mean of species diversity of patches and temporal variability at either the patch or aggregate scales in an analysis of data from 62 plant communities. Pfestorf et al (2013) and Debouk, de Bello, and Sebastià (2015) both reported finding a more direct coupling between environmental drivers and plant functional traits than diversity. Aggregate ANPP in our study was stabilized through time by attributes linked to species identity and dominance rather than by species richness.…”
Section: Links Between Attributes and Anpp Variabilitymentioning
confidence: 99%
“…Because nitrogen is one of the important resources for plants to grow [33,34], and N addition can improve soil nitrogen availability which promotes the photosynthesis of plants [10,35]. Additionally, SLA was positively correlated with plant growth rates and reflected light capture and plant growth [36], and high SLA suggests that plants have a strong ability to maintain nutrition [14,37]. N supply promotes the photosynthesis of plants and results in high SLA, and accordingly low LDMC was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Plant functional traits are important in ecology, because they can respond to changes in environmental conditions at the individual level and also affect ecosystem structure and function [13,14]. Recently, plant functional traits have been documented in response to climate changes [15] and grazing [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…A (meteorological) drought, i.e. a period with below average precipitation, often accompanied by high atmospheric vapour pressure deficits (Dai, 2011), typically results in low water availability in the soil, limiting plant growth and affecting plant interactions and vegetation structure (Morecroft et al, 2004, Debouk et al, 2015. Previous summer droughts have been shown to reduce ecosystem productivity throughout Europe (Ciais et al, 2005) and they are predicted to increase in Central and Southern Europe in the next decades, with up to 40% less precipitation in summer in 2071-2100 (Dankers and Hiederer, 2008) (Fig.…”
Section: Biodiversity Loss and Droughtmentioning
confidence: 99%